Identifikasi Mikroplastik pada Ikan Tongkol Lisong (Auxis Rochei) dan Ikan Tuna Makarel (Euthynnus Affinis) di Pangkalan Pendaratan Ikan (PPI) Oeba, Kupang - Larasati, Gendhis; Wuri, Diana A.; Kallau, Novalino H. G. (JURNAL KAJIAN VETERINER, 2024)
Waste management in Kupang City is still very poor. The waste will eventually reach the sea and will be degraded into microplastics. Microplastics, which are less than 5 millimetres in size, are made from plastic waste in marine waters through physical, mechanical, chemical and biological processes. This research was conducted to determine the characteristics (shape and colour) and abundance of microplastics found in digestive tract samples, and meat/muscle samples of lisong tuna (Auxis rochei) and mackerel tuna (Euthynnus affinis) obtained from PPI Oeba, Kupang City. Each organ was extracted using 10% KOH for 48-72 hours and microplastic characteristics were observed visually using a stereo microscope. The research results found microplastics in the digestive tract and meat of A. rochei and E. affinis. The forms found in digestive tract A. rochei include films and fragments, with transparent colours. Meanwhile in meat, fragments, films and fibres were found in red, blue, black, transparent and purple. The forms found in digestive tract E. affinis include fragments, pellets, fibers and films with blue, black, transparent and yellow colours. Meanwhile in meat, fragments and pellets were found with black and yellow colors. The abundance of microplastics detected in digestive tract A. rochei included 1.2 MP/individual, while in meat it was 0.2 MP/gr. In E. affinis it includes 0.8 MP/individual in digestive tract and in meat 0.06 MP/gr.